Survival Probability and Predictors of Under-Five Mortality in Siaya County, Western Kenya - Owuor, Harun Odhiambo (JOOUST, 2024)
Approximately 1 in 26 children worldwide die before the age of five, with more than 50% of these deaths occurring in sub-Saharan Africa. In Kenya, despite gains in reducing under-five mortality from 52 to 41.9 deaths per 1000 live births between 2015 and 2022, this rate remains notably higher than the Sustainable Development Goal (SDG) 3 target of 25 deaths per 1000 by 2030. The impact of interventions on risk factors and socio-structural inequities have varied across regions, indicating potential effects of unaddressed issues. There is a need to further understand the key drivers of under-5 mortality in given contexts to help improve intervention effectiveness. Siaya County is one of the regions with high under-five mortality, 63 deaths per 1,000 live births as compared with the national rate of 41 deaths per 1000 live births. The broad objective of this study was to estimate the survival probability and determine predictors of under-five mortality in Siaya County. Specifically, it estimated the survival probability; and determined the socioeconomic, maternal healthcare-seeking, and environmental predictors of under-five mortality in Siaya County. The study utilized secondary data from the Siaya Health Demographic Surveillance System from 2015 to 2020 data set. This is an annual population-based longitudinal surveillance. The data on predictors and child survival of children born within the six years of the study were retrieved. The total number of observations was 24452, representing the number of live births born within the study period. The male-to-female ratio was 1:1, with 1,540 (6.3%) children dying before celebrating their fifth birthday. The cumulative survival probability among children under five was approximately 90% with children of younger age being at increased risk of death. In Cox multivariable analysis, the risk of death among females was 18 times (HR 0.82 CI=0.74, 0.91 p <0.001) lower than male children. Under-five mortality decreased with increasing educational attainment of the mother (HR 0.40 CI 0.23, 0.70 p <0.001) and number of ANC visits (HR 0.48 CI 0.26, 0.88 p= 0.018). Delivery in the hospital (p= 0.001); birth over age 18 years (p= 0.034) and use of a modern or pit latrine (p=0.03) improved survival. In conclusion, the hazard of death among children under the age of five years was higher at an early age. Female gender, low maternal education attainment, fewer number of ANC visits, maternal age, delivery in hospital, and toilet use were associated with higher under-five mortality. These observations reinforce the need to target multiple components at the community and institutional levels.
Keywords: Under-Five Mortality; Mortality